Penegakan Hukum Perkara Tindak Pidana Ringan (Tipiring) dengan Pendekatan Restorative Justice yang Ditolak Pihak Korban di Kepolisian Resor (Polres) Lahat - Hambali Yusuf; Sri Suatmiati; Sega Ortega (Jurnal Hukum Lex Generalis, 2024)
The restorative justice approach (restorative justice) is a breakthrough to realize legal justice that humanizes humans by using conscience which also fights the negative stigma in society, that the law is blunt upwards, but sharp downwards, so that cases that are simple and trivial or light can be resolved outside the court do not need to be submitted to the court. The research problem is how is the law enforcement of minor criminal cases with a restorative justice approach that is rejected by the victim in the Lahat Resort Police and what factors hinder the handling of minor criminal cases with a restorative justice approach at the Lahat Resort Police. The research uses an empirical juridical approach complemented by literature data and the nature of this research is descriptive analytical. The result of the research is in the handling of minor criminal cases with a restorative justice approach at Lahat Police Station carried out as usual according to the Indonesian criminal justice system, namely by preventive action using non-penal means or also repressive action with penal means. For handling tipiring cases, Lahat Police investigators prioritize and prioritize the restorative justice (RJ) approach. However, if the use of the restorative justice approach is rejected by the victim or the perpetrator after the mediation step is attempted in such a way as to be guided by the provisions of Articles 5 and 6 of the Indonesian National Police Regulation Number 8 of 2021, but still fails, then the case file is forwarded to the next stage, namely being submitted to the prosecutor's office. The obstacle factors encountered by the Lahat Police investigating officers include the weak rules regarding restorative justice that are not enough to guarantee legal certainty, because they are still in the form of regulations under the law (legal factors), the lack of understanding of investigating officers regarding restorative justice, where the police still believe that law enforcement must be in accordance with the criminal justice system and the professionalism of investigating officers is still low (apparatus factors) and the lack of understanding, knowledge and understanding of the community about the importance of using restorative justice in resolving tipiring cases (community factors).